2011
DOI: 10.1289/ehp.1002835
|View full text |Cite
|
Sign up to set email alerts
|

Residential Proximity to Freeways and Autism in the CHARGE Study

Abstract: BackgroundLittle is known about environmental causes and contributing factors for autism. Basic science and epidemiologic research suggest that oxidative stress and inflammation may play a role in disease development. Traffic-related air pollution, a common exposure with established effects on these pathways, contains substances found to have adverse prenatal effects.ObjectivesWe examined the association between autism and proximity of residence to freeways and major roadways during pregnancy and near the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
267
3
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(288 citation statements)
references
References 65 publications
13
267
3
5
Order By: Relevance
“…The impair ment of neurite outgrowth by nPM is consistent with epidemiological evidence of developmental effects of air pollution in children (Perera et al 2009;Suglia et al 2008), which include an association with autism (Volk et al 2010). The interaction of nPM with glutamatergic (NMDA) excito toxicity suggests that cerebral ischemia, which also involves glutamatergic excito toxicity, could be exacerbated by nPM.…”
Section: Il-1α Tnfαsupporting
confidence: 75%
See 1 more Smart Citation
“…The impair ment of neurite outgrowth by nPM is consistent with epidemiological evidence of developmental effects of air pollution in children (Perera et al 2009;Suglia et al 2008), which include an association with autism (Volk et al 2010). The interaction of nPM with glutamatergic (NMDA) excito toxicity suggests that cerebral ischemia, which also involves glutamatergic excito toxicity, could be exacerbated by nPM.…”
Section: Il-1α Tnfαsupporting
confidence: 75%
“…Cognitive impairments of school-age children have been associated with exposure to black carbon (BC), a marker for vehicle-derived PM (Suglia et al 2008). Also, a prospective study of children showed associations of lower IQ with prenatal exposure to vehicle-derived polycyclic aromatic hydrocarbons (PAHs) (Perera et al 2009), and autism prevalence was associated with residential proximity at birth to urban freeways (Volk et al 2010). Rodent models also show varying memory impairment after exposure to ozone (Avila-Costa et al 1999;Dorado-Martinez et al 2001;Guerrero et al 1999;Rivas-Arancibia et al 2010) and vehiclederived air pollutants (Zanchi et al 2010).…”
mentioning
confidence: 99%
“…Windham et al (2006) reported a positive relation between the distribution of hazardous air pollutants at birth addresses and ASD among children in California. Other studies in California found that living close to freeways and traffic-related air pollution in mother's late pregnancy or child's first year of life was associated with an increased risk for autism (Volk et al, 2011(Volk et al, , 2013. Siddique et al (2011) compared children living in the New Delhi (India) urban area with children living in rural areas and showed that ADHD was positively correlated with current PM 10 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal smoking correlates with socio-economic factors such as education and income (Kabir et al, 2011;Laaksonen et al, 2005) and may contribute to this association. The earlier studies (Calderon-Garciduenas et al, 2011;Guxens et al, 2012;Siddique et al, 2011;Volk et al, 2011;Vrijheid et al, 2012;Windham et al, 2006) Odds ratios and 95% confidence intervals of neurodevelopmental outcomes by residential address-based NO x (black circles) and PM 10 (black hollow diamonds) levels. The spikes represent odds ratios for outcomes of interest and cap lines indicate 95% confidence intervals.…”
Section: Figurementioning
confidence: 99%
“…The third trimester of pregnancy appears to have the strongest association with the health impact of the concentration of air pollutants on autism [66]. Living near a freeway was associated with autism [90]. Traffic sources of air pollution were significant in the study by Becerra et al [6].…”
Section: Health Effects Of Air Pollutionmentioning
confidence: 99%